Rádio, indústria cultural e rizomas periféricos Kaxinawá: uma rádio de resistência na baixada - BASTOS, Marcus Alexandre de Pádua Cavalcanti (2015)
This research has the object to characterize the community radio Kaxinawá as cultural industry will instrument of resistance. For the analysis of this radio was held initially a presentation of the historical development of radio activity in the world until his arrival in Brazil, which took place through the elites, as well as its popularization and operation as industry. From the radio industry and relationship, we present the concept of cultural industry, developed by Adorno and Horkheimer, addressing the economic and ideological interests that permeate the creation of cultural products. In order to explain even more the importance of ideological interests, search the concept of hegemony, Gramsci, from which it is stated that the cultural industry can work as a private apparatus of hegemony, contributing to hegemonic common values. In Brazil, the focus is put on large radio vehicles dominated by oligopolies media. From that moment, there is the main concern of this research is to understand how community radio can be considered a counterpoint to the cultural industry. At first, we sought from that question, make a historical survey of the origin of the movements that gave beginning the free and community radios worldwide. Soon will follow, this was to reflect on the arrival of the movement in the country, its dissemination and expansion. It will be observed that the history of community radios in the country is marked by debates and disagreements between state, business and communication society. The reflections on the theme of conflict resulted in the legalization through the Law 9,612 / 98. Subsequent to this, we intend to reflect on how their communication capabilities can make this media a dispute space and resistance providing opportunities for a new look, reshaping and transforming the existing communication processes. For this we used the concept of counterhegemony Gramsci and the rhizome of Deleuze and Guattari as theorists operators to analyze the practices of community radio stations and especially the need to invest in an alternative form of communication, thus presenting the possibility of subversion the unilateralism promoted by the cultural industry. Our goal aims will reflect on how critical theory influences contemporary communication processes and the extent to which community media - such as radio - can be viewed as a counterpoint to the cultural industry of design.